AB0631 Anti-Rna Polymerase III and anti Pm/Scl Antibodies: Prevalence and Clinical Associations in A Large Cohort of Spanish Patients with Systemic Sclerosis. (10th June 2014) - Iniesta, N.; Espinosa, G.; Fonollosa, V.; Tolosa, C.; Egurbide, M.V.; Sáez Comet, L.; Ortego, N.; Rodríguez Carballeira, M.; Trapiella, L.; Simeόn, C.P.
Abstract : Background: Some authors postulate that systemic sclerosis's (SSc) heterogenic expression is mostly conditioned by the positivity to any of its specific auto-antibodies. Objectives: To assess the prevalence of anti-RNA-polymerase III (RNA-pol III) and anti-Pm-Scl (Pm-Scl) antibodies in a large SSc patient cohort included in the Spanish Scleroderma Study Group (SSSG), and to correlate with the clinical manifestations. Methods: From January 1996 to June 2013, 1399 patients fullfilling LeRoy and Medsger criteria for SSC were included in the SSSG database. Demographic, clinical (visceral involvement), immunological, and capillaroscopic data were compared, according to the serologic status of RNA-pol III and Pm-Scl. Results: 34 out of 179 patients (18.9%) tested positive for RNA-pol III. Among RNA-pol III positive patients, female gender was less common (79% vs 93%, p=0.02) and diffuse cutaneous subtype of SSc was more frequent (39% vs 19%, p=0.02). We did not find any difference in terms of mean age at clinical onset, mean age at diagnosis, mean disease duration, first manifestation at disease onset or cumulative manifestations. Sclerodermic renal crisis (SRC) was similar in both groups (18% vs 6.3%, p=0.15). Survival at 5, and 10 years was not different in both groups (93% vs 94.2%, p=0.72 and 84% vs 88%, p=0.41, respectively). Regarding Pm-Scl, 53 out of 684 patients (7.7%) were positive. We did not find any differences in terms of mean age at clinical onset, mean age at diagnosis, mean disease duration, first manifestation at disease onset or cumulative manifestations. Pm-Scl positive patients had more frequently puffy fingers (10% vs 2.2%, p=0.009), and myositis (32% vs 8.4%, p<0.001). In addition, ground-glass pattern on computerized tomography lung scan was more common (61% vs 34%, p=0.001) and less forced vital capacity (%) (78±21 vs 85±23) (p=0.04). However, there was no difference in the prevalence of interstitial lung disease (57% vs 47%, p=0.19). There was a higher prevalence of SRC in the Pm-Scl group (11% vs 2.2%, p=0.03). There was no difference between Pm-Scl positive and negative patients in terms of survival at 5 and 10 years (93.4% vs 96.6%, p=0.24 and 89.5% vs 91.3%, p=0.59, respectively). We found other SSc specific antibodies in RNA-pol III patients (6 with anti-centromere and 4 with anti-topoisomerase antibodies). Among Pm-Scl positive patients, 6 of them also tested positive for anti-centromere and 8 for anti-topoisomerase antibodies. 5 patients had both RNA-pol III and Pm-Scl antibodies. Conclusions: In Spanish SSc patients, seropositivity for RNA-pol III patients did not correlate with SRC. The presence of anti-Pm-Scl antibodies was associated with muscular involvement. Neither RNA-pol III nor Pm-Scl antibodies were related to worse prognosis. References: Steen V. Autoantibodies in systemic sclerosis. Semin Arthritis Rheum. 2005 Aug;35(1):35-42. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4098